Asian cities in the 21st century:- Contemporary approaches to municipal management :Fighting urban poverty - Villareal Mildred; Hamid Naved (Asian Development Bank Philippines, 2001)
proceedings of a forum in Shanghai, People's Republic of China, 26-29 June 2000
Keywords: Urban Povery Issues -- Urban poor -- Low-income housing - -- Employment -- Reducing poverty through partnership -- Slum improvements -- Providing housing for the poor -- Improving service delivery to the poor -- Networking -- Urban waste management